Understanding non-routine discharge: Factors that are associated with premature termination from higher levels of care in adults with anorexia nervosa. Issue 6 (2nd November 2022) - Gorrell, Sasha; Rienecke, Renee D.; Duffy, Alan; Huston, Emma; Mehler, Philip S.; Johnson, Craig; Manwaring, Jamie; McClanahan, Susan; Blalock, Dan V.; Le Grange, Daniel
ABSTRACT: This study sought to replicate and extend associations between clinical and demographic features at admission and types of premature treatment termination for adults diagnosed with anorexia nervosa (AN) in higher-level-of-care settings. Secondary data analyses examined a study population comprised of adults with AN ( N  = 565) who were admitted to one of two United States eating disorder treatment centers (April 2015–April 2020) for intensive outpatient, partial hospitalization, residential, or inpatient services. There were no significant differences in the type of non-routine discharge according to level of care. At admission, those with lower BMI were more likely to discharge against medical advice, and those with lower cognitive restraint and elevated binge eating were more likely to discharge against medical advice or by staff-initiated request, respectively. Discharge by parent/patient request was more likely among those who were older or who reported lower baseline desire for muscularity. Overall older age, elevated binge eating, and lower weight, desire for muscularity, and cognitive restraint may be associated with less tolerance/acceptability for AN treatment. Increased understanding of how to better support patients who admit to higher levels of care with these clinical features will contribute to better odds of completion of a full course of treatment. Clinical implications: Inpatient services showed less routine discharges compared to other levels of care Level of care does not appear to associate with a specific type of discharge Factors associated with premature discharge include older age and elevated binge eating Lower weight, desire for muscularity, and restraint associate with premature discharge Patients who admit with lower restraint and BMI are more likely to discharge against medical advice